2023
DOI: 10.1007/s00228-023-03476-6
|View full text |Cite
|
Sign up to set email alerts
|

Results from a first-in-human study of dersimelagon, an investigational oral selective MC1R agonist

Abstract: Purpose To describe outcomes from the first-in-human study of dersimelagon, an investigational oral selective MC1R agonist, under development for the treatment of erythropoietic protoporphyria (EPP) and X-linked protoporphyria (XLP). Methods In this double-blind, placebo-controlled phase 1 study, the safety, tolerability, pharmacokinetics, and pharmacodynamics of single and multiple ascending oral doses of dersimelagon in healthy participants were evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The first-in-human phase 1 trial conducted for dersimelagon enrolled 144 healthy participants (143 completed the trial) and demonstrated an acceptable safety profile in these patients [ 44 ]. Thirty-four of these patients received a placebo, with the remaining patients receiving at least one dose of dersimelagon (doses ranged from 1 to 600 mg).…”
Section: Key Clinical Trial Results For Dersimelagonmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-in-human phase 1 trial conducted for dersimelagon enrolled 144 healthy participants (143 completed the trial) and demonstrated an acceptable safety profile in these patients [ 44 ]. Thirty-four of these patients received a placebo, with the remaining patients receiving at least one dose of dersimelagon (doses ranged from 1 to 600 mg).…”
Section: Key Clinical Trial Results For Dersimelagonmentioning
confidence: 99%
“…The most common TEAEs reported were related to skin pigmentation, including lentigo, skin hyperpigmentation, and melanocytic nevi (two cases were severe but non-malignant). Additionally, there were no statistically significant effects of age or race on the pharmacokinetics of dersimelagon; however, increased exposure was observed in females compared to males, which was attributed to differences in the body weight generally observed in male versus female participants [ 44 ].…”
Section: Key Clinical Trial Results For Dersimelagonmentioning
confidence: 99%
“…In 2019, the Food and Drug Administration (FDA) approved EPP in the USA and in 2020 EPP was approved in Australia. A new promising molecule MT-7117 (dersimelagon) is under investigation as an oral alternative to afamelanotide for adults and adolescents [ 37 ].…”
Section: Skin Diseases With the Use Of Afamelanotidementioning
confidence: 99%